New social and professional competences of the university educational environment in connection with the introduction of innovative teaching methods - Соколовська, Ірина Анатоліївна; Sokolovskaya, I. A.; Соколовская, И. А. (Минск : БГУ, 2020)
The article deals with the actual problem of the active introduction of distance learning systems in medical schools as one of the new pedagogical conditions for the training of competitive specialists. In addition, the subjective attitude to this innovation is justified and the possible consequences of the impact of online courses on the quality of future physician training are predicted. В статье рассмотрена актуальная проблема активного внедрения в программы обучения вузов системы дистанционного обучения как одного из новых педагогических условий подготовки конкурентоспособных специалистов. Кроме того, дано обоснование субъективному отношению к данному новшеству и прогнозирование возможных последствий по влиянию онлайн-курсов на качество подготовки будущих специалистов высших учебных заведений.
Новые социальные и профессиональные компетенции образовательной среды вуза в связи с внедрением инновационных методов обучения
Keywords: distance learning; education; competencies; the problem of quality training; дистанционное обучение; высшее образование; компетенции; проблема качественной подготовки